(untitled) (FULafia Journal of Science and Technology, 2018)
Cloud computing has a unique ability to provide on-demand metered elastic computing resources to multi-tenant users. However, given the nature of the cloud platform and its present limited ways to detect unauthorized access or modifications to data,cloud users and data owners therefore do not trust that their data is adequately secure on the cloud platforms. This paper presents a technique of data coloring for securing data on cloud platforms based on establishing and using concatenated fingerprints for cloud watermarking. Using the technique, cloud users and data-owners secure their data by first coloring it offline before uploading onto any cloud platform and subsequently they can detect any unauthorized modifications or identify paths of any unauthorized data modifications